Rancang Bangun Sistem Informasi Kepegawaian pada PT Garuda Asia Semesta - Valencia, Stefanny; Kesuma, Dorie P (Universitas Multi Data Palembang, 2025)
The purpose of creating the attendance application at PT Garuda Asia Semesta is to provide a solution for attendance that previously used name cards, transforming it into a computerized system through a web-based application. This web based application serves as a medium for managing attendance. The development of this web application is done using Visual Studio Code for programming and stores its data in a MySql database. The methodology employed in the development of this application is the RUP (Rational Unified Process) method. The outcome of this application is expected to assist Human Resources and facilitate account users in utilizing the system that has been built.